The Role of ATC’s Situational Awareness in Wildlife Hazard Handling at the Aerodrome Control Unit Tower - Aldela Ayu Titi Nurhawani; Imam Sonhaji; Dhian Supardam (Journal of Information Technology, computer science and Electrical Engineering, 2024)
The handling of wildlife hazard is an important aspect in ensuring flight safety at the Aerodrome Control Tower Unit of AirNav Indonesia, Denpasar’s Branch. In this context, situational awareness becomes a key factor that influences decision-making and actions of ATCs regarding wildlife hazard. This research aims to analyze the role of ATC's situational awareness in handling wildlife hazard at the mentioned unit. Data collection methods include field observations, interviews, and document analysis. The research findings indicate that wildlife hazard incidents at the I Gusti Ngurah Rai International Airport are quite high, but the lack of detection by ATCs poses a problem that can disrupt the smooth flow of air traffic services. This is primarily due to high workload and insufficient situational awareness of the dangers posed by wildlife hazard. Recommended solutions include conducting regular briefings, launching campaigns on wildlife hazard awareness, and enhancing situational awareness among ATCs. The research results are expected to provide insights and recommendations for improving flight safety concerning wildlife hazard at the Aerodrome Control Tower Unit of AirNav Indonesia, Denpasar’s Branch.